Religious Leaders and Gender Mainstreaming in Bekasi: Reading Local Religious Authority through Fatima Mernissi’s Critique - Daan Dini Khairunida (Jurnal Ilmiah Guru Madrasah, 2026)
Religious leaders play an important role in shaping community understandings of gender relations in Muslim societies, particularly where religious authority remains closely connected to everyday social life. This article examines how religious leaders participate in gender mainstreaming in Kampung Jati Kaum, Tanjung Sari Village, North Cikarang District, Bekasi Regency, and reads this role through Fatima Mernissi’s critique of patriarchal interpretation. A descriptive qualitative design was used, with data collected through semi-structured interviews, participant observation, and supporting documentation. Eighteen informants participated in the research, consisting of six religious leaders and twelve community members. The data were analysed using the interactive model of Miles, Huberman, and Saldaña, with attention to recurring themes such as religious authority, domestic and public roles, conditional participation, contextual interpretation, and patriarchal assumptions. The findings show that religious leaders occupy a central position as normative mediators in the formation of gender norms. Their views fall into three broad tendencies: traditional, moderate, and progressive. Traditional views preserve domestic-public divisions, moderate views allow women’s participation under moral and domestic conditions, while progressive views connect women’s education and public participation with Islamic principles of justice and mutual responsibility. Through Mernissi’s critique, the article shows that gender mainstreaming in this community is shaped by negotiation between Islamic ethical values and inherited patriarchal cultural assumptions. The article argues that local religious authority can either reproduce gender hierarchy or open space for gradual gender-just reinterpretation.